(untitled) - Giarratano, Joseph (Boston, MA, 2005)
The new edition of this market-leading text builds upon the blend of expert systems theory and application established in earlier editions. The first half of the book concentrates on the theoretical base of expert systems, and offers a broad overview of Artificial Intelligence and its relation to expert systems. The second half of the text focuses on application, with the introduction of the CLIPS expert systems tool, and its new object-oriented language, COOL. All chapters end with an extensive problem set designed to reinforce knowledge
Keywords: Expert systems ( Computer science ),Rule-based programming